Challenges in STEM Learning: A Case of Filipino High School Students - Rogayan Jr., Danilo V.; Rafanan, Renzo Jay L; De Guzman, Clarisse Yimyr (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
STEM education faces monumental challenges which are aggravated by the Industrial Revolution (IR) 4.0 and the current COVID-19 global contagion. These challenges also affect how students learn in the STEM discipline in the senior high school. This qualitative study employed a case research design which sought to investigate nature of the challenges in STEM learning among senior high school students in the Philippines. Semi-structured interview guide was used in gathering the qualitative data from the 20 STEM learners in a government-run secondary school in Zambales, Philippines. Findings showed that the students encountered challenges in the STEM program. Ten themes emerged based on the students’ responses. These challenges encountered by the students revolved around three categories – course-related challenges, individual challenges and socio-cultural challenges. The study recommends that schools offering STEM academic strands may reframe and rethink their processes, practices and policies to address the students’ challenges in STEM learning. Policy recommendations are also discussed in the paper to equip the students towards the demands of Industrial Revolution 4.0 and in the post-pandemic world.